Diastereo- and enantioselective preparation of cyclopropanol derivatives - Simaan, Marwan; Marek, Ilan (Beilstein Journal of Organic Chemistry, 2019)
The diastereoselective carbocupration reaction of alkoxy-functionalized cyclopropene derivatives, followed by a subsequent trapping of the resulting cyclopropylmetal species with an electrophilic source of oxygen (oxenoid) afforded various tetrasubstituted cyclopropanol derivatives in high diastereo- and enantiomeric ratios. Similarly, the enantioselective copper-catalyzed carbomagnesiation/oxidation (or amination) sequence on achiral nonfunctionalized cyclopropenes provided the desired cyclopropanol (and cyclopropylamine) derivatives in excellent diastereo- and enantiomeric excesses.
Keywords: carbocupration; cyclopropanol; cyclopropene; regioselectivity; stereoselectivity

(untitled) - D’yakonov, V. A.; Trapeznikova, O. A.; de Meijere, A.; Dzhemilev, U. M. (Chem. Rev., 2014)

(untitled) - Salaün, J.; Bairds, M. S. (Curr. Med. Chem., 1995)

(untitled) - Wong, H. N. C.; Hon, M.-Y.; Tse, C.-W.; Yip, Y.-C.; Tanko, J.; Hudlicky, T. (Chem. Rev., 1989)

(untitled) - Haym, I.; Brimble, M. A. (Org. Biomol. Chem., 2012)

(untitled) - Orellana, A.; Nikolaev, A. (Synthesis, 2016)

(untitled) - Kulinkovich, O. G. (Chem. Rev., 2003)

(untitled) - Magrane, J. K., Jr; Cottle, D. L. (J. Am. Chem. Soc., 1942)

(untitled) - Imamoto, T.; Kamiya, Y.; Hatajima, T.; Takahashi, H. (Tetrahedron Lett., 1989)

(untitled) - Ito, S.; Shinokubo, H.; Oshima, K. (Tetrahedron Lett., 1998)

(untitled) - Rubottom, G. M.; Lopez, M. I. (J. Org. Chem., 1973)

(untitled) - Murai, S.; Aya, T.; Sonoda, N. (J. Org. Chem., 1973)

(untitled) - Du, H.; Long, J.; Shi, Y. (Org. Lett., 2006)

(untitled) - Fontani, P.; Carboni, B.; Vaultier, M.; Maas, G. (Synthesis, 1991)

(untitled) - Pietruszka, J.; Widenmeyer, M. (Synlett, 1997)

(untitled) - Hussain, M. M.; Li, H.; Hussain, N.; Ureña, M.; Carroll, P. J.; Walsh, P. J. (J. Am. Chem. Soc., 2009)

(untitled) - Imai, T.; Mineta, H.; Nishida, S. (J. Org. Chem., 1990)

(untitled) - Benoit, G.; Charette, A. B. (J. Am. Chem. Soc., 2017)

(untitled) - Barluenga, J.; Suero, M. G.; Pérez-Sánchez, I.; Flórez, J. (J. Am. Chem. Soc., 2008)

(untitled) - Ukai, K.; Oshima, K.; Matsubara, S. (J. Am. Chem. Soc., 2000)

(untitled) - Matsubara, S.; Ukai, K.; Fushimi, H.; Yokota, Y.; Yoshino, H.; Oshima, K.; Omoto, K.; Ogawa, A.; Hioki, Y.; Fujimoto, H. (Tetrahedron, 2002)

(untitled) - Cheng, K.; Carroll, P. J.; Walsh, P. J. (Org. Lett., 2011)

(untitled) - Turro, N. J. (Acc. Chem. Res., 1969)

(untitled) - Salaun, J. (Chem. Rev., 1983)

(untitled) - Salaün, J.; Bennani, F.; Compain, J. C.; Fadel, A.; Ollivier, J. (J. Org. Chem., 1980)

(untitled) - Stolle, A.; Ollivier, J.; Piras, P. P.; Salaün, J.; de Meijere, A. (J. Am. Chem. Soc., 1992)

(untitled) - Trost, B. M.; Bogdanowicz, M. J. (J. Am. Chem. Soc., 1973)

(untitled) - Trost, B. M.; Bogdanowicz, M. J. (J. Am. Chem. Soc., 1973)

(untitled) - Longone, D. T.; Wright, W. D. (Tetrahedron Lett., 1969)

(untitled) - Kulinkovich, O. G.; Sviridov, S. V.; Vasilevskii, D. A.; Pritytskaya, T. S. (Zh. Org. Khim., 1989)
J. Org. Chem. USSR 1989, 25, 2027.

(untitled) - Kulinkovich, O. G.; Sviridov, S. V.; Vasilevski, D. A. (Synthesis, 1991)

(untitled) - Sviridov, S. V.; Vasilevskii, D. A.; Savchenko, A. I.; Pritytskaya, T. S.; Kulinkovich, O. G. (Zh. Org. Khim., 1991)
J. Org. Chem. USSR 1991, 27, 250.

(untitled) - Vasilevskii, D. A.; Savchenko, A. I.; Sviridov, S. V.; Kulinkovich, O. G. (Zh. Org. Khim., 1991)
J. Org. Chem. USSR 1991, 27, 1249.

(untitled) - Savchenko, I. A.; Kulinkovich, O. G. (Zh. Org. Khim., 1997)
Russ. J. Org. Chem. 1997, 33, 846.

(untitled) - Savchenko, A. I.; Shevchuk, T. A.; Kulinkovich, O. G. (Zh. Org. Khim., 1999)
Russ. J. Org. Chem. 1999, 35, 225.

(untitled) - Lee, J.; Kim, H.; Cha, J. (J. Am. Chem. Soc., 1996)

(untitled) - Epstein, O. L.; Savchenko, A. I.; Kulinkovich, O. G. (Tetrahedron Lett., 1999)

(untitled) - Kananovich, D. G.; Kulinkovich, O. G. (Tetrahedron, 2008)

(untitled) - Lee, J.; Kang, C. H.; Kim, H.; Cha, J. K. (J. Am. Chem. Soc., 1996)

(untitled) - Kasatkin, A.; Sato, F. (Tetrahedron Lett., 1995)

(untitled) - Corey, E. J.; Rao, S. A.; Noe, M. C. (J. Am. Chem. Soc., 1994)

(untitled) - Kulinkovich, O. G.; Kananovich, D. G.; Lopp, M.; Snieckus, V. (Adv. Synth. Catal., 2014)

(untitled) - Welch, J. G.; Magid, R. M. (J. Am. Chem. Soc., 1967)

(untitled) - Lukina, M. Y.; Rudavshevskaya, T. Y.; Nesmeyanova, O. A. (Dokl. Akad. Nauk. SSSR, 1970)

(untitled) - Avezov, I. B.; Bolesov, I. G.; Levina, R. Y. (J. Org. Chem. USSR, 1975)

(untitled) - Moiseenkov, A. M.; Czeskis, B. A.; Semenovsky, A. V. (J. Chem. Soc., Chem. Commun., 1982)

(untitled) - Lehmkuhl, H.; Mehler, K. (Justus Liebigs Ann. Chem., 1978)

(untitled) - Lehmkuhl, H.; Mehler, K. (Liebigs Ann. Chem., 1982)

(untitled) - Richey, H. G.; Watkins, E. K. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Watkins, E. K.; Richey, H. G. (Organometallics, 1992)

(untitled) - Stoll, A. T.; Negishi, E.-i. (Tetrahedron Lett., 1985)

(untitled) - Rubin, M.; Rubina, M.; Gevorgyan, V. (Chem. Rev., 2007)

(untitled) - Lautens, M.; Klute, W.; Tam, W. (Chem. Rev., 1996)

(untitled) - Marek, I.; Simaan, S.; Masarwa, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Miege, F.; Meyer, C.; Cossy, J. (Beilstein J. Org. Chem., 2011)

(untitled) - Rubin, M.; Rubina, M.; Gevorgyan, V. (Synthesis, 2006)

(untitled) - Isaka, M.; Nakamura, E. (J. Am. Chem. Soc., 1990)

(untitled) - Delaye, P.-O.; Didier, D.; Marek, I. (Angew. Chem., Int. Ed., 2013)

(untitled) - Roy, S. R.; Didier, D.; Kleiner, A.; Marek, I. (Chem. Sci., 2016)

(untitled) - Liao, L.-a.; Fox, J. M. (J. Am. Chem. Soc., 2002)

(untitled) - Nakamura, M.; Hirai, A.; Nakamura, E. (J. Am. Chem. Soc., 2000)

(untitled) - Liu, X.; Fox, J. M. (J. Am. Chem. Soc., 2006)

(untitled) - Krämer, K.; Leong, P.; Lautens, M. (Org. Lett., 2011)

(untitled) - Rubin, M.; Gevorgyan, V. (Synthesis, 2004)

Carbocyclic Three-Membered Ring Compounds - Baird, M. S. (Georg Thieme Verlag, 1996)

(untitled) - Petiniot, N.; Anciaux, A. J.; Noels, A. F.; Hubert, A. J.; Teyssié, P. (Tetrahedron Lett., 1978)

(untitled) - Panne, P.; Fox, J. M. (J. Am. Chem. Soc., 2007)

(untitled) - Díaz-Requejo, M. M.; Mairena, M. A.; Belderrain, T. R.; Nicasio, M. C.; Trofimenko, S.; Pérez, P. J. (Chem. Commun., 2001)

(untitled) - Lipshutz, B. H.; Wilhelm, R. S. (J. Am. Chem. Soc., 1982)

(untitled) - Lipshutz, B. H.; Kozlowski, J.; Wilhelm, R. S. (J. Am. Chem. Soc., 1982)

(untitled) - Lipshutz, B. H.; Wilhelm, R. S.; Floyd, D. M. (J. Am. Chem. Soc., 1981)

(untitled) - Minko, Y.; Marek, I. (Org. Biomol. Chem., 2014)

(untitled) - Boche, G.; Lohrenz, J. C. W. (Chem. Rev., 2001)

(untitled) - Müller, E.; Töpel, T. (Ber. Dtsch. Chem. Ges. B, 1939)

(untitled) - Boche, G.; Möbus, K.; Harms, K.; Lohrenz, J. C. W.; Marsch, M. (Chem. – Eur. J., 1996)

(untitled) - Möller, M.; Husemann, M.; Boche, G. (J. Organomet. Chem., 2001)

(untitled) - Warner, P.; Lu, S.-L. (J. Org. Chem., 1976)

(untitled) - Surry, D. S.; Spring, D. R. (Chem. Soc. Rev., 2006)

(untitled) - Simaan, M.; Delaye, P.-O.; Shi, M.; Marek, I. (Angew. Chem., Int. Ed., 2015)

(untitled) - Minko, Y.; Pasco, M.; Lercher, L.; Botoshansky, M.; Marek, I. (Nature, 2012)

(untitled) - Minko, Y.; Pasco, M.; Lercher, L.; Marek, I. (Nat. Protoc., 2013)

(untitled) - Davies, H. M. L.; Lee, G. H. (Org. Lett., 2004)

(untitled) - Marek, I.; Simaan, S.; Masarwa, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Dian, L.; Müller, D. S.; Marek, I. (Angew. Chem., Int. Ed., 2017)

(untitled) - Parra, A.; Amenós, L.; Guisán-Ceinos, M.; López, A.; García Ruano, J. L.; Tortosa, M. (J. Am. Chem. Soc., 2014)

(untitled) - Müller, D. S.; Marek, I. (J. Am. Chem. Soc., 2015)

(untitled) - Panek, E. J.; Kaiser, L. R.; Whitesides, G. M. (J. Am. Chem. Soc., 1977)

(untitled) - DeBergh, J. R.; Spivey, K. M.; Ready, J. M. (J. Am. Chem. Soc., 2008)

(untitled) - Zhang, D.; Ready, J. M. (Org. Lett., 2005)

(untitled) - Simaan, M.; Marek, I. (Angew. Chem., Int. Ed., 2018)

(untitled) - Sommer, H.; Marek, I. (Chem. Sci., 2018)

(untitled) - Dian, L.; Marek, I. (Angew. Chem., Int. Ed., 2018)

(untitled) - Müller, D. S.; Werner, V.; Akyol, S.; Schmalz, H.-G.; Marek, I. (Org. Lett., 2017)